Ijtihād al-‘Ulamā’ al-Indūnīsīyīn wa Taṭwī al-Fiqh - Karim, Helmy (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1994)
Ijtihad as thinking or reasoning to solve problems that can not be found in the detailed explanation of the Qur'an and Sunnah, is an open and universal concept. But in practice ijtihad can not be separated from the situation where and when he was done. Therefore it is very conditional execution diligence, and sometimes very local.In the Indonesian context, ijtihad done them by the Fatwa Commission, the Indonesian Ulema Council (MUI), the issues can not be separated from the context of the Indonesian-ness. Then the extent of ijtihad MUI contribute to the development of Islamic law in both the substance and methodology?DOI: 10.15408/sdi.v1i2.858